Marketing Strategy: Efektivitas Wom Dan Stp Terhadap Pengembangan Akun Instagram @Moodshelter - Al Zuhri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Social media has become one of the tools used to communicate with audiences which functions to provide public services, for example the Instagram platform. The use of features on the Instagram platform is optimized to be able to gain exposure from the content produced. This research aims to conduct an experiment to see what impact can be generated from managing Instagram using marketing strategies by reviewing aspects of Instagram planning, utilization and maintenance of published content based on the use of marketing strategies including Word of Mouth (WoM) and Segmenting, Targeting, Positioning (STP) as well as the use of hashtags, management posting schedule, and templates. The method used in this research is qualitative. Data collection is carried out through observation and documentation by applying Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis. The results of this research show that maintaining an Instagram account using marketing strategies has proven to be effective in increasing account reach and the number of viewers, followers, likers, as well as visits to Instagram profiles